Fifty shades of Grey [videorecording (DVD)] - Johnson, Dakota, 1989-; Dornan, Jamie, 1982-; Ehle, Jennifer, 1969-; James, E. L. (Universal Studios Home Entertainment, 2015)
Ana is an inexperienced college student tasked with interviewing enigmatic billionaire Christian Grey. But what starts as business quickly becomes an unconventional romance. Swept up in Christian's glamorous lifestyle, Ana soon finds another side to him as she discovers his secrets and explores her own dark desires. What results is a thrilling, all-consuming romance as Christian and Ana test the limits they will go to for their relationship.